EFFECT OF 5-AMINOLEVULINIC ACID AND GENISTEIN ON ACCUMULATION OF POLYPHENOL AND ANTHOCYANIN IN ‘QINYANG’ APPLES - L. Chen; Y. R. Guo; G. Bai; J. J. Sun; Y. Li (Journal of Animal and Plant Sciences, 2015)
Consumers are highly interested in purchasing apples with red color. However, the early-ripening apples always show poor color, so it is particularly important to improve apple color. The study was aimed to investigate effects of 5- Aminolevulinic acid (ALA) and/or Genistein (GNT) on apple peel color of ‘Qinyang’, polyphenol compounds and regulation of the gene related to anthocyanin synthesis. 300 mg·L-1 ALA and/or 21.62μg·L-1 GNT were sprayed on ‘Qinyang’ apples every five days after their bags were removed. The concentrations of anthocyanin and total polyphenol were determined with spectrophotometer and the concentrations of anthocyanin and polyphenol components were determined by HPLC. The relative expressions of six anthocyanin-related structural genes and regulation factor MYB10 were measured by RT-PCR. Spraying ALA and/or GNT had significant promoting effects on anthocyanin accumulation of apple peel. The contents of anthocyanin with ALA, GNT, and ALA plus GNT sprayed were 1.12, 1.37, and 3.00 times as much as that with water sprayed, respectively. ALA and/or GNT played an important role in promoting total polyphenol accumulation, and the flavonoids concentrations of apple peel were significantly increased. The RT-PCR results revealed that ALA and/or GNT up-regulated the expressions of PAL, CHS, DFR, F3H, UFGT, LDOX and MYB10.
Keywords: Apple; 5-Aminolevulinic acid; Genistein; Anthocyanin; Polyphenol; Gene expression